Replacement of fish oil with a high-DHA algal oil in a fishmeal-free diet fed to Florida pompano (Trachinotus carolinus) - Riche, Marty; Barrows, Frederic T.; Nilles, Zachary; Mejri, Sahar; Campbell, Kelly; Wills, Paul S. (Frontiers in Aquaculture, 2023)
A 12-week growth trial was conducted to evaluate the complete co-replacement of fish meal (FM) and fish oil (FO) in juvenile Florida pompano (Trachinotus carolinus) diets. Five open-formula experimental diets were formulated as iso-nitrogenous (approximately 46% crude protein) and iso-lipidic (approximately 15% crude lipid). It is assumed that Florida pompano lack the mechanisms for synthesizing sufficient LC-PUFA. In the FM/FO-free diets, to meet the necessary dietary intake of LC-PUFA, a commercially available Schizochytrium algal oil was used. Four diets were prepared from a basal mix, with spirulina and poultry by-product meal as the principal protein sources. They differed only in their oil source, containing fish oil (FO), algal oil (AO), soy oil (SO), or a 50/50 blend of algal oil and soy oil (A/S). The fifth experimental diet (control) was a standard open-formula FM diet. In addition to the experimental diets, two commercial closed-formula diets served as references. The seven diets, each with four replicates, were stocked with 20 Florida pompano (approximately 4 g) in each. The experimental open-formula diets were tested against the control using Dunnett’s t-test, and different oil sources were tested against each other using orthogonal contrasts. The four experimental diets were each tested against the two reference diets with equivalency tests. Feed intake and survival were not different between the experimental diets and control. However, all production metrics were lower in the SO diet than the control. No other differences were observed between the FO, AO, and A/S diets and the control, or between the three diets. The feed conversion ratio (FCR) was higher in fish fed the SO diet than in fish fed the control diet, and no other differences were found. The protein efficiency ratio (PER) was higher in fish fed the control diet than in fish fed the experimental diets. Protein productive values (PPV) were similar to PER, except that the PPV in fish fed the AO diet was not different from the control. The contrasts revealed that the FO, AO, and A/S diets resulted in a lower FCR than the SO diet. The PER was higher in fish fed the AO diet, and lower in fish fed the SO diet. The PPV was higher in fish fed the AO diet than in fish fed the A/S and SO diets, but similar to that of fish fed the FO diet. There were striking differences in performance between the two commercial reference feeds, underscoring the importance of using well-defined open-formula diets as a reference or control. To our knowledge this is the first study to demonstrate that co-replacement of FM and FO can be achieved in Florida pompano by supplying an FM- and FO-free diet. The development of successful open-formula diets without FO will help spur innovation and sustainability in aquaculture production.